Long Period Fiber Grating Inscribed in Hollow-Core Photonic Bandgap Fiber for Gas Pressure Sensing - Jian Tang; Zhe Zhang; Guolu Yin; Shen Liu; Zhiyong Bai; Zhengyong Li; Mi Deng; Ying Wang; Changrui Liao; Jun He; Wei Jin; Gang-Ding Peng; et al. (IEEE Photonics Journal, 2017)
In this paper, we have proposed and experimentally prepared an improved gas pressure sensing device. It is mainly constructed by a short hollow silica tube segment and a CO2-laser-induced long period grating in hollow-core photonic bandgap fiber (HC-PBF). To effectively enhance the interaction between light in the air-core of HC-PBF and external surroundings, thus to achieve the best possible gas pressure sensitivity, a microchannel is introduced in the middle of the hollow silica tube segment with the femtosecond laser processing technique. The corresponding gas pressure experiments demonstrate that the resonant wavelength of the LPFG shows a blue shift up to −1.3 nm/MPa. Moreover, the temperature response sensitivity of this sensor is as low as 5.3 pm/°C and enable it possible as a temperature-insensitive gas pressure measure apparatus.